Decalepis hamiltonii root fraction alleviates CCl4 hepatotoxicity in a rat model - Sonali Labhade; Smita Jain; Sohan Chitlange; Sarvesh Paliwal; Swapnil Sharma (Journal of Ayurveda and Integrative Medicine, 2023)
Background: Decalepis hamiltonii (D. hamiltonii) is Indian folk medicine in herbal preparations, to reduce appetite, and cures dysentery, bronchitis, uterine hemorrhage, and other ailments. Objective: The current investigation focused on the hepatoprotective effect of D. hamiltonii roots fractions against liver damage. Materials and methods: The current research discussed the fraction from D. hamiltonii root extracts was used. Male Wistar rats (albino strain) were grouped into 4 distinct groups of six animals each. Group I: plain water and vehicle whereas Group II (CCl4 control): CCl4 (1 ml/kg, 20 % v/v in olive oil) over 7 days and vehicle; Over 7 days, Group III received Silymarin 100 mg/kg/day and tap water with 20 % v/v of CCl4, whereas Group IV (treatment group) received DHE 50 mg/kg/day, 100 mg/kg/day, and water. Assessment of biochemical parameters, Mitochondrial modulation, gene expression analysis, and RT-PCR, was used to estimate the protective action of DHEF in CCl4-intoxicated rats. Results: The administration of CCl4 increased levels of total bilirubin (0.63 ± 0.97 mg/dl) plasma amino transferases (110.36 ± 1.13 U/L, 86.56 ± 2.41 U/L and 1.51 ± 1.36 mg/dl respectively) which were mitigated by D. hamiltonii treatment. Activity like Lipid peroxidation and content of nitric oxide also augmented, while the antioxidant action measured by GSH (9.64 ± 0.18 U/mg protein), SOD (3.69 ± 0.22 U/mg protein), and CAT (1.47 ± 0.01 U/mg protein) was reduced. Decalepis hamiltonii root provided substantial restoration of GSH (14.92 ± 0.04 nmol/gm protein), SOD (4.20 ± 0.18 U/mg protein), and CAT (2.71 ± 0.04 U/mg protein) levels. In addition, the acute phase reactants stimulated by CCl4 administration enhanced mRNA expressions of IL-6, IL-10, TNF-a, NF-κβ, and COX-2, which were enhanced by D. hamiltonii treatment. Conclusions: In summary, DHEF protects the liver against CCl4-induced damage, possibly by mitochondrial modulation mechanism. These findings indicate that D. hamiltonii significantly moderates oxidative stress of CCl4-induced hepatotoxicity.